Survival at 1, 3, and 5 Years in Diabetic and Nondiabetic Patients on Hemodialysis (Iranian Journal of Kidney Diseases, 2010)
We analyzed survival of 185 adult patients on maintenance hemodialysis (9 h/wk to 12 h/wk) at Emam Khomini Hospital in Ahvaz, Iran. Patient survival at 1, 3, and 5 years was 89.2%, 69.2%, and 46.8%, respectively. There was no significant difference between diabetic and nondiabetic patients in 1-year survival (87.1% versus 89.7%, P = .66). But, 3- and 5-year survival rates of diabetic patients were significantly lower than those of nondiabetic patients (52.2% versus 73.8%, P = .04; zero versus 56.9%, P < .001; respectively). Based on our findings, the survival of diabetic patients undergoing hemodialysis was much worse than survival of nondiabetic patients. Thus, prevention of diabetic nephropathy should be more emphasized; and if end-stage renal disease is present, other renal replacement therapies such as kidney transplantation must be considered as soon as possible.